Religious Coping and Health and Well-Being among Jews and Muslims in Israel. Issue 3 (2nd July 2020) - Abu-Raiya, Hisham; Sasson, Tali; Pargament, Kenneth I.; Rosmarin, David H.
ABSTRACT: This cross-sectional study used data from 486 Israeli Jews and Muslims to examine the phenomenon of religious coping among an Israeli sample. Participants were recruited in the context of two research projects on coping methods, one examining the stress of the Gaza war of 2014, and the other examining the stress of aging. Participants provided demographic information and completed measures of religious coping, satisfaction with life, and depressive symptoms. Findings revealed that: (1) with relatively minor modifications, the Brief RCOPE, through which religious coping was assessed in this study, has the same 2-factor structure among Israelis, both Jews and Muslims; (2) positive and negative religious coping correlated moderately, but their association varied according to religious affiliation (i.e., Muslims vs. Jews) and religious self-definition (secular vs. traditional vs. religious); (3) negative religious coping was related to lower life satisfaction and higher depressive symptoms, whereas positive religious coping was related to none of the outcome measures; (4) religious affiliation and religious self-definition appeared as moderators of the link between positive religious coping and life satisfaction, and religious self-definition as a moderator between negative religious coping and life satisfaction, and; (5) neither religious affiliation nor religious self-definition moderated the links between both types of religious coping and depressive symptoms.